(untitled) (Quest Journal of Management and Social Sciences, 2019)
Background: Hopefully, if rest of things work as expected, the adequate supply of electricity, as one of the major industrial energy inputs, plays vital role in determining the industrial production, at large. In this paper, the present researchers assumed that the present state of scarcity of electricity may reveal their higher level of willingness to pay for higher energy efficient ratio as a pay-off of their improved industrial productivity. It is a proven fact that as one of the dominant indicators of national economic development and prosperity, effective electricity management procedures for industry increases significantly the productivity and operational efficiency. Objectives: The present paper attempts to explore the willingness of industrialists to pay more for adequate electricity supply for the industrial purpose in the present context of Nepal. Methods: Extensive desk review was carried out with a directed intension to develop insights on effective management of energy supply-related activities in industrial sector by analyzing the advances and trends as well as synergies in different intervention areas. Findings: A large number of academic and professional research works are carried out by different researchers on electricity management, with focus on identification of energy management models, corresponding to the industrial sector that shows individual attributes, social contexts, as well as participation and knowledge, which can have cumulative effect on WTP.WTP for adequate electricity is one of the key measures for sustainable economic growth for reliable and sensible management of forecasted energy demand. Conclusions: In spite of plethora of literature on electricity management and WTP, the solutions presented by different researchers are limited in scope. Still many researchers are working on tool contributions, but most of them are only providing solutions for specific regions and communities. There is a need to develop a generic electricity management system with tracing the industrialists’ willingness to pay for adequate electricity supply in a customized manner as a generic solution. The present researcher is hopeful that this work accomplishes this need. Implications: Required strict policy regulations at governing level and effective programming at implementation at industry level.